(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Physicians working in dedicated COVID-19 hospitals face enormous stress due to high patient loads, ethical dilemmas, miscommunication, and the demanding nature of pandemic healthcare. Work stress can negatively impact physicians’ well-being, patient care quality, and overall healthcare outcomes. This study aimed to assess the work stress among physicians in COVID-19 hospitals and examine its association with their background characteristics. Methods: The cross-sectional study was conducted in three dedicated COVID-19 hospitals in Dhaka city; Kuwait Bangladesh Friendship Hospital, Kurmitola General Hospital, and Mugda Medical College Hospital. Data were collected from 168 physicians using a semi-structured questionnaire. Statistical analyses, including t-tests, ANOVA, and chi-square tests, were performed using SPSS. Results: Among the respondents, 50.6% had mild stress, while 49.4% had moderate stress (Mean±SD=65.14±10.27) requiring better management. Work stress was higher among unmarried physicians (75.6%), younger age (24-29 years) groups (56%) and those with lower monthly income. Gender, religion, and family type did not show significant associations with work stress. Conclusion: A substantial proportion of physicians experienced moderate stress, highlighting the need for effective workplace interventions. Strategies such as improving work environments, ensuring adequate rest, providing psychological support, and offering incentives can help to mitigate work stress following exposure to any public health emergency like COVID-19. JOPSOM 2024; 43(2): 61-67